Strategic Human Capital Deployment: Examining the Mechanisms Linking Managerial Talent, Work Experience Accumulation, and Supervisory Effectiveness to Job Rotation Outcomes - Dwianto, Agung Surya; Kusuma, Sitta (Ilomata International Journal of Management, 2026)
This study examines the influence of managerial talent, work experience accumulation, and supervisory effectiveness on job rotation outcomes among managers of PT Pos Indonesia Regional IV Jakarta. As a state-owned enterprise operating in an increasingly competitive logistics environment, PT Pos Indonesia requires evidence-based human capital strategies to enhance managerial adaptability and organizational agility. This research proposes an integrated structural model linking managerial talent, experiential learning, and supervisory practices, with a particular emphasis on their sequential interrelationships in explaining job rotation effectiveness. A quantitative approach was employed using a census of 160 managers. Data were analyzed through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to test direct and indirect relationships among variables. The findings indicate that managerial talent, work experience accumulation, and supervisory effectiveness positively influence job rotation outcomes. In addition, managerial talent indirectly affects job rotation effectiveness through work experience and supervision, suggesting a sequential mediation mechanism. While the results provide empirical support for the proposed model, they should be interpreted with caution due to the study’s cross-sectional design, reliance on self-reported data, and focus on a single regional context. This study contributes to the talent management literature by highlighting the importance of integrating managerial capability, experiential accumulation, and supervisory processes into a coherent mechanism influencing job rotation outcomes. Practically, the findings offer guidance for designing competency-based rotation systems to strengthen leadership pipelines and organizational resilience in state-owned enterprises.